Knowledge, attitude and practice regarding voluntary blood donation among Mawlana Bhashani Science and Technology University students in Bangladesh - Hossain, Md. Imam; Easmin, Nilufar; Rahman, Shafiqur; Islam, Meskatul; Salam, Abdus (International Journal of Basic & Clinical Pharmacology, 2018)
Background: In developing countries like Bangladesh, the demand of blood supply is increasing every year. To ensure safe and adequate blood supply and to motivate voluntary donors in blood donation processes, this study was aimed to assess the knowledge, attitude and practice of blood donation among Mawlana Bhashani Science and Technology University students in Bangladesh. Methods: A cross-sectional study was conducted among 403 students (200 females and 203 males), using a self administered structured questionnaire. Results: 59.05% students had good knowledge about blood donation. The knowledge score was significantly higher (p<0.05) in female than male. Students positive attitudes toward voluntary blood donation included- blood donation saves life (62.8% strongly agreed, 32% agreed), donation is a moral activity (57.1% strongly agreed, 37.5% agreed), young are more suitable to donate blood (40% strongly agreed, 49.1% agreed), the best way of donation is voluntary non-remunerated (22.3% strongly agreed, 41.4% agreed). Their negative attitudes included - best way to donate blood is at the request of relatives (24.3% strongly agreed, 38% agreed), donation in paid (only 3% strongly agreed, 10.7% agreed) or something in exchange (only 1% strongly agreed, 8.9% agreed) and blood donors contract disease (3.5% strongly agreed, 27.8% agreed). Among the participants 34.2% donated blood and males donated significantly more than females (p<0.001). Physically females were significantly unfit for donating blood (p<0.001). Conclusions: Although having positive attitudes blood donation practice is not substantial among students especially in females. Interactive awareness and motivation packages should be created to enhance voluntary blood donation.